RUANG KETIGA TERSELUBUNG JALAN BLORA, JAKARTA PUSAT - Jason Bryan Johanes; Mekar Sari Suteja (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Being in the area around Jendral Sudirman street, which is one of Jakarta’s business districts, should have a good effect on the surrounding areas. The good effect of the development of Sudirman Street is the creation of various new economic spaces, even though the Blora Street area is increasingly being degraded due to its inability to develop like the surrounding areas. Even though it is located in the TOD (Transit Oriented Development) area of Dukuh Atas, which is an intersection between several modes of public transportation and a high mobility point, it does not immediately make the Blora Street area come alive again. This area is located on the edge of the Sudirman Flyover which is not directly visible from the main road, so the area becomes quiet because it does not have good visibility from the main road. This project aims to revive the area with a new building that can fulfill aspects of regional life. The site location is also a transitional space between the economic area of Blora Street and the residential area behind it so that the site can be used as access. As a less developed transitional space, the site was developed into a third space that functions as a communal space and other activities without forgetting its main function as an economic area that is directly related to the TOD area as a mobility center. With this project, the area can again become bustling with a new paradigm of the third space which focuses on life primarily as a space for interaction, communication, economy, and creativity of each individual in one place. Keywords:  Blora Street; Third Space;  TOD Abstrak Berada di daerah sekitar Jalan Jendral Sudirman yang merupakan salah satu distrik bisnis Jakarta, semestinya memberikan efek baik terhadap wilayah-wilayah di sekitarnya. Efek baik dari perkembangan Jalan Sudirman adalah dengan terciptanya beragam ruang ekonomi baru, walaupun kenyataannya, kawasan Jalan Blora semakin lama semakin terdegradasi akibat ketidakmampuannya untuk berkembang seperti wilayah-wilayah di sekitarnya. Meskipun berada di kawasan TOD (Transit Oriented Development) Dukuh Atas yang merupakan persimpangan antara beberapa moda transportasi umum dan menjadi titik mobilitas yang tinggi, tidak langsung membuat kawasan Jalan Blora ini menjadi ramai dan kembali hidup. Kawasan yang berada di tepian Fly Over Sudirman tidak terlihat secara langsung dari jalan utama sehingga kawasan menjadi sepi karena tidak memiliki visibilitas yang baik dari jalan utama. Tujuan adanya proyek ini adalah untuk menghidupkan kembali kawasan dengan suatu bentuk bangunan baru yang dapat memenuhi aspek-aspek kehidupan kawasan. Titik lokasi tapak juga merupakan ruang transisi antara kawasan ekonomi Jalan Blora dengan kawasan hunian yang ada di belakangnya sehingga tapak dapat dimanfaatkan sebagai akses. Sebagai ruang transisi yang kurang berkembang, tapak dikembangkan menjadi ruang ketiga yang berfungsi sebagai ruang komunal maupun kegiatan lainnya tanpa melupakan fungsi utama sebagai kawasan ekonomi yang berhubungan langsung dengan kawasan TOD sebagai pusat mobilitas. Dengan adanya proyek ini, kawasan dapat kembali menjadi ramai dengan paradigma baru ruang ketiga yang memfokuskan kehidupan utamanya sebagai ruang interaksi, komunikasi, ekonomi, serta kreativitas setiap individu dalam satu wadah.